2020
DOI: 10.1101/2020.06.15.152397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diet-regulated production of PDGFcc by macrophages controls energy storage

Abstract: Metazoans have evolved specialized fat-storing tissues dedicated to the dynamic storage of energy. Fat tissues in mammals consist of lipid-storing adipocytes, macrophages, and stromal cells. Macrophages are tightly associated with adipocytes yet, their function in fat remains enigmatic. We report that resident, but not bone-marrow-derived, macrophages are critical for establishment and control of fat stores in metazoans. Mice lacking resident macrophages form adipocytes but fail to store lipids or to expand li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 83 publications
2
22
0
Order By: Relevance
“…A lipid receptor known as Trem2 has been identified as one of the master regulators of lipid‐associated macrophage function, helping to prevent both adipocyte hypertrophy and systemic metabolic imbalance (Jaitin et al , 2019 ). An evolutionarily conserved pathway was recently discovered in resident macrophages that control fat storage via PDGFcc secretion (preprint: Cox et al , 2020 ), which underlines their importance in maintaining the functionality of the WAT cellular microenvironment. Another study elegantly demonstrated not only the close vasculature association of ATMs and their contribution to endocytosis but also identified a clear anti‐inflammatory/detoxifying gene signature (Silva et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A lipid receptor known as Trem2 has been identified as one of the master regulators of lipid‐associated macrophage function, helping to prevent both adipocyte hypertrophy and systemic metabolic imbalance (Jaitin et al , 2019 ). An evolutionarily conserved pathway was recently discovered in resident macrophages that control fat storage via PDGFcc secretion (preprint: Cox et al , 2020 ), which underlines their importance in maintaining the functionality of the WAT cellular microenvironment. Another study elegantly demonstrated not only the close vasculature association of ATMs and their contribution to endocytosis but also identified a clear anti‐inflammatory/detoxifying gene signature (Silva et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, by buffering fluctuations in tissue lipid levels, adipose tissue- and liver-resident macrophages help to maintain metabolic homeostasis ( 5 , 10 , 11 ). Moreover, it was recently demonstrated that adipose-tissue-resident macrophages (ATMs) facilitate lipid storage within white adipocytes, providing an additional means by which ATMs contribute to metabolic homeostasis ( 12 ). Secondly, increased tissue lipid levels can lead to triacylglycerol (TG) accumulation and inflammation within macrophages, thereby contributing to the development of metabolic dysfunction ( 13 , 14 ).…”
mentioning
confidence: 99%
“…In terms of macrophage origin, the traditional view believed that bone marrow-derived mononuclear macrophages (also known as recruited macrophages) are recruited into damage tissue via chemokine (C-C motif) receptor 2 (Ccr2) in response to chemokines and inflammatory signals and affect wound healing by secreting inflammatory factors such as TNFα ( 58 ) ( 64 ). Ccr2 encodes a receptor for monocyte chemoattractant protein-1, a chemokine that specifically mediates monocyte chemotaxis, and is expressed on monocytes and macrophages, but not in microglia or tissue resident macrophage at the resting state ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Even scar-resident oligodendrocytes obstructed axon extension through secreted Ntm. Additionally, the traditional view is that scar-resident macrophages come from the blood supply ( 58 ) ( 64 ). But recent studies have shown that monocytes after spinal cord injury can come from adjacent skull and spine bone marrow ( 66 ).…”
Section: Discussionmentioning
confidence: 99%